“Beer is Haram!” Representation of Islam by Online Newspapers in Malaysia on The Issue of Better Beer Festival & Oktoberfest - Mohd Raqib Sofian; NurulNadirah Abu Hasan; Afiqah Mior Kamarulbaid; Muhd Zaki Mustafa; Nurul Fathihin Mohd Noor Shah; Norsimaa Mustaffa (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by Scopus/MyCite